The Association Between the Subjective Exercise Experience of Chinese Women Participating in Square Dance and Group Cohesion: The Mediating Effect of Income - Sun, Yuting; Ji, Peiyao; Wang, Yan; Fan, Hongying (Frontiers in Psychology, 2021)
Background: Chinese square dance has become well known worldwide in recent years, and most participants are women who dance with a group in their communities. In particular, middle-aged women may have physical and mental health problems, and participating in square dance may increase women’s positive subjective well-being and decrease their negative emotions, which may improve their health over the long-term. In addition, participating in square dance can promote group cohesion. Our study aimed to examine the relationship between the subjective exercise experience of participating in square dance and group cohesion and whether some variables (e.g., age, education, duration, income level and work) play a role as mediators in the association with subjective exercise experience and group cohesion. Methods: In total, 1,468 Chinese women from 31 provinces and 82 cities participated in this study by completing an online questionnaire. The questionnaire consisted of a subjective exercise experience questionnaire and a group environment questionnaire. We analyzed the collected data and built a statistical model. Results: (a) Square dance satisfied women’s physical and psychological needs partly; (b) positive well-being was positively correlated with group cohesion, and fatigue was negatively correlated with group cohesion; and (c) the income level was a partial mediator of the relationship between group cohesion and subjective exercise experience. Conclusion: Chinese women have different motivations for participating in square dance. Because this activity can help meet women’s physical and psychological needs, an increasing number of individuals worldwide participate in square dance. As women’s subjective well-being increases, group cohesion increases, and vice versa. Moreover, the subjective exercise experience remains a significant predictor of group cohesion after including income level as a mediator, suggesting that the model indicates partial mediation.